"Efectividad de medios de difusión para incentivar la asistencia de madres a un programa de estimulación temprana" - Juárez Rodríguez, Jacob Jefte (2017)
The present quantitative, quasiexperimental, cross, of unknown selection. It aimed to determine the effectiveness of visual broadcast media: poster and flyer, to increase assistance of mothers at early stimulation program between the months of August and September 2016 in hospital I La Esperanza. The sample population consisted of 151 assistance’s mothers to the events scheduled selected for inclusion criteria. The data collection was applied by an attendance registry of mothers. The information obtained was tabulated and analyzed with statistical methodology, the pictures are presented in tables of double entry, statistical analysis was performed using. According to the results it came to the following conclusion: The average attendance of 1 person per day for the poster and 9 people per day for the steering wheel, making clear the difference in effectiveness between the two and the value of significant p (0.000) <0.05 value so the alternative hypothesis is accepted, the average of the number of attendees per poster was lower than average attendance per steering wheel. It is more efficient diffusion flyer program by poster.